Application of Cervical Arthroplasty With Bryan Cervical Disc: 10-Year Follow-up Results in China. Issue 2 (January 2016) - Zhao, Yanbin; Zhang, Yilong; Sun, Yu; Pan, Shengfa; Zhou, Feifei; Liu, Zhongjun
Abstract : Study Design: Retrospective study. Objective: The aims of this study were to evaluate the radiographic and clinical outcomes of Bryan cervical disc arthroplasty at 10-year follow-up. Summary of Background Data: Cervical arthroplasty is a new technique for treating degenerative cervical disease. Previous reports have shown that cervical arthroplasty with Bryan disc gained good clinical outcomes at 4- to 6-year follow-up. Methods: Clinical outcomes and dynamic x-ray examination were evaluated at baseline and at final follow-up. Results: Thirty-three patients with complete clinical and radiographic data were included in this study. The mean follow-up period was 120.5 months (116–130 months). Twenty-five patients underwent single-level arthroplasty and 7 underwent arthroplasty at 2 levels. One patient underwent arthroplasty at 3 levels. Eight of the 33 patients presented with radiculopathy and 25 patients with myelopathy. The 42 levels of surgery included C3/4 (3 levels), C4/5 (7 levels), C5/6 (26 levels) and C6/7 (6 level). The mJOA score of the 25 patients with myelopathy was 11.8 at the baseline and 15.9 at the final follow-up. No patient suffered from adjacent segment disease. Two patients received revision surgeries at the index level for recurrent radiculopathy caused by osteophyte formation and heterotopic ossification. On x-ray examination, the range of motion at the operated level was 7.8 degree at the baseline and 4.7 degree at the final follow-up. Heterotopic ossification was observed in 29 (69.0%) levels and heterotopic ossification of Grade 4 was observed in 14 levels. Adjacent segment degeneration was observed in 30 (47.6%) levels. Conclusion: Cervical arthroplasty using Bryan cervical disc prosthesis resulted in fine clinical outcomes in this study. Heterotopic ossification was common after Bryan disc arthroplasty, which decreased the range of motion. Level of Evidence: 4